Versus: Is it possible to talk about an error? The culturally induced error in the Peruvian legislation - Villavicencio, Felipe (2015)
Cultural diversity is one of the biggest challenges that contemporary Law is facing. From this state of things, the penal regulation takes particular relevance, due to its burdensome towards who has committed a crime. A question arises about if it is possible to condemn someone due to the valoration that a different culture made about a specific behavior.In the present versus, there is a discussion about how to understand article 15 of the peruvian Criminal Code, and if the option chosen by the national system of justice is suitable to face the aforementioned problem.